Bartın ilindeki kadın girişimcilerin sorunları ve çözüm önerileri - Morkoç, Hülya (Bartın Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Geçmişte girişimcilik kâr elde etme ile birlikte kendi işini kurabilme ve iş alanını büyütme olarak ifade edilmiş olsa da günümüzde girişimcilik risk alabilme, iş dünyasındaki yenilikleri takip etme, imkânları değerlendirme ve iş hayatına yansıtma süreci olarak tanımlanmıştır. Tarihsel süreç boyunca girişimcilik ülkelerin ekonomik kalkınma ve sürdürülebilirlik süreçlerinde önemli rol oynayan bir unsurdur. Bilhassa sanayi toplumundan bilgi toplumuna geçişle beraber bu önem giderek artış göstermiştir. Türkiye'de son yıllarda girişimciliğe önemli derecede destek verilmiş ve kadın girişimciliği büyük önem kazanmıştır. Türkiye'de 2000 yılından bu yana kadın girişimciliğine yönelik önemli programlar ve uygulamalar devlet ve özel sektör dâhil tüm kurumlarda uygulanmaya başlamıştır. Girişimci kadınların iş hayatına atılmaları ile birlikte yeni sektörler geliştirilmiş ve beraberinde bu süreç ekonomik kalkınmaya pozitif etki sağlamıştır. Bu bağlamda hem dünyada hem de Türkiye'de kadın girişimci ekonomiyi canlandırmada ve yön vermede önemli rol üstlenmiştir. Araştırmanın amacı, Bartın ilinde faaliyet gösteren kadın girişimcilerin sorunlarını tespit etmek ve sorunlara istinaden çözüm önerileri geliştirmektir. Çalışmanın evrenini Bartın ilinde faaliyet gösteren kadın girişimciler oluşturmaktadır. Örneklemi ise kolayda örneklem tekniği ve Bartın ilinde faaliyet gösteren 150 kadın girişimciden oluşmaktadır. Araştırmaya ilişkin verilerin elde edilmesinde yüz yüze anket yöntemine başvurulmuştur. Bu kapsamda kadın girişimcilere anket yapılmış ve sonuçlar ANOVA, t-testi, Mann Whitney U-testi, Kruskal Wallis H-testi ve Korelasyon analizlerinden faydalanılarak çözümlenmiştir. Araştırmanın sonucunda kullanılan ölçek, faaliyet öncesi sorun yaşama ve/veya ekonomik sorun yaşama, faaliyet öncesinde bilgi eksikliği ve toplumsal sorun yaşama, faaliyet sırasında sorun yaşama ile bilgi eksikliği ve toplumsal sorun yaşama, faaliyet sırasında ekonomik sorun yaşama son olarak aile yaşamında yaşanan sorunlar gibi alt başlıklar çerçevesinde oluşturulmuştur. Kadın girişimci sorunlarının tespit edilmesi ve uygun çözüm önerilerinin geliştirilmesi adına hazırlanmış bu çalışmada demografik ve girişimcilik bilgilerinden elde edilen bulgular çerçevesinde işletmede çalışan kişi sayısında anlamlı bir farklılık bulunmaz iken yaş, eğitim, medeni durumu, çocuğu olma durumu, iş kurmadan önceki uğraşları, ailede girişimci olma durumları açısından da anlamlı farklılıklar tespit edilmiştir

In the past, entrepreneurship has been defined as the ability to establish one's own business and expand the business area together with making a profit, but today, entrepreneurship is defined as the process of taking risks, following the innovations in the business world, evaluating opportunities and reflecting them on business life. Throughout the historical process, entrepreneurship is an element that plays an important role in the economic development and sustainability processes of countries. Especially with the transition from the industrial society to the information society, this importance has gradually increased. In Turkey, a significant amount of support has been given to entrepreneurship in recent years and women's entrepreneurship has gained great importance. In our country, since 2000, important programs and practices for women's entrepreneurship have started to be implemented in all institutions, including the state and private sector. With the entry of entrepreneur women into business life, new sectors have been developed and this process has had a positive effect on economic development. In this context, women entrepreneurs have played an important role in reviving and directing the economy both in the world and in Turkey. The aim of the research is to identify the problems of women entrepreneurs operating in the province of Bartın and to develop solutions for the problems. The universe of the study consists of women entrepreneurs operating in the province of Bartın. Its sample consists of convenience sampling technique and 150 women entrepreneurs operating in the province of Bartın. Face-to-face survey method was used to obtain the data related to the research. In this context, women entrepreneurs were surveyed and the results were analyzed using ANOVA, t-test, Mann Whitney U-test, Kruskal Wallis H-test and Correlation analysis. The scale used as a result of the research has sub-dimensions such as experiencing problems before the activity and/or experiencing economic problems, lack of information and social problems before the activity, experiencing problems during the activity and lack of information and social problems, economic problems during the activity and finally problems in family life. was created within the framework of the titles. In this study, which was prepared to identify the problems of women entrepreneurs and to develop appropriate solution proposals, there was no significant difference in the number of people working in the enterprise within the framework of the findings obtained from demographic and entrepreneurship information, while there was no significant difference in the number of people working in the enterprise, such as age, education, marital status, having a child, occupations before starting a business, being an entrepreneur in the family. There were also significant differences in terms of status.
Problems and solution suggestion of women entrepreneurs in Bartin province
Keywords: Bartın; Girişimcilik; Kadın girişimciliği; Türkiye; Entrepreneurship; Women's entrepreneurship; Turkey